Why did Bodhidharma go to the east? Buddhism’s struggle with the mind in the world - Garfield, Jay L. (Sophia, 2006)
This question—why did Bodhidharma come from the West?— is ubiquitous in Chinese Ch’an Buddhist literature. Though some see it as an arbitrary question intended merely as an opener to obscure puzzles, I think it represents a genuine intellectual puzzle: Why did Bodhidharma come from theWest—that is, fromIndia? Why couldn’tChina with its rich literary and philosophical tradition have given rise to Buddhism? We will approach that question, but I prefer to do so backwards. I want to ask instead, “why was it so fortuitous for the development of Buddhist philosophy that Bodhidharma wentEast? I will argue that by doing so he gave a trajectory to Buddhist thought about the mind and knowledge that allows certain issues that are obscure in Indo-Tibetan Buddhism, despite their centrality to the Buddhist critique of Indian orthodoxy, to come into sharper relief, and hence to complete a project begun, but not completable, in that Indo-European context.